What color is your paratext? - Bilder G; Rathemacher AJ (Serials Librarian)
In the final vision session of the 2009 NASIG Annual Conference, Geoffrey Bilder from CrossRef discussed the problem of how to identify trustworthy scholarly information on the Internet. This problem is exacerbated by readers' growing distrust of intermediaries such as publishers and librarians, by the fact that the Internet lacks the traditions that have developed in scholarly communication to ensure trust, and by the sheer amount of information now readily available. Paratext is understood as anything outside of a text that sets expectations about that text. In the past, paratext, for example a publisher logo, provided important clues as to the trustworthiness of information. In the context of the Internet, Bilder suggested creating a meta-brand to serve as paratext. CrossRef is developing a meta-brand called CrossMark that would certify for the reader that the online content to which it is attached has been vetted by processes of scholarly review and is therefore trustworthy.